Agrourbanism Tools for Governance and Planning of Agrarian Landscape - Gottero, Enrico; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a much needed overview of the agrourbanism topic in the context of territorial studies. It carefully looks at rural, urban, periurban farming in both professional and unprofessional capacities as one of the main sustainable forms of land use and management. This cutting edge text explores the various forms of agricultural and urban planning, as well as the main innovations that the agro-urban approach entails in terms of governance, spatial dimensions and functions. Agrourbanism provides a breadth of information and serves as a practical study of concerns facing policy and decision makers, planners and landscape managers, as well as farmers, managers of protected areas, local authorities and local action groups. As such this book is suitable as a course accompaniment to provide an overview of the complexity of agro-urban issues.
Chapter 1. Approaching a vision of agrarian urbanism: innovative domains, key definitions and concepts (Enrico Gottero) -- Part 1: Agrourbanism from a global perspective -- Chapter 2. Farmland preservation and rural development in Canada (Sara Epp) -- Chapter 3. Managing Urban and Rural Agricultural Landscape Processes in Japan (Chika Takatori) -- Chapter 4. Cities linked through food trans-boundaries: The case of Singapore as an Agri-pelago (Jessica Anna Diehl) -- Part 2: Governing the agro-urban spaces in Europe -- Chapter 5. Contraposition, juxtaposition and transposition of the urban and the rural (Marco Santangelo) -- Chapter 6. Towards and effective implementation of the Green Infrastructure in rural areas. Challenges and options for a substantial integration with spatial planning (Carlo Rega) -- Chapter 7. Spatial dimensions of the CAP: territorial congruence, supposed and explicit territoriality (Enrico Gottero) -- Chapter 8. Foodscape and food urbanism in Europe: the urban-rural interface (Susan Parham) -- Part 3: Agrourbanism forms and places -- Chapter 9. Urban agriculture forms in Europe (Frank Lohrberg) -- Chapter 10. Agricultural Park in Europe as tool for agri-urban policies and design: a critical overview (David Fanfani) -- Chapter 11. Urban agriculture in Urban Food Policies: debate and practices (Giacomo Pettenati) -- Chapter 12. Preserving and restoring Italian traditional rural landscapes. Addresses from social perception to spatial planning, policies and research (Bianca Maria Seardo) -- Part 4: Agrourbanism functions and tools -- Chapter 13. Towards countryside revival: reducing impacts of urban expansion on land benefits (Marco Marchetti) -- Chapter 14. Ecosystems Services and spatial planning: lessons learned from the Life SAM4CP project (Carolina Giaimo) -- Chapter 15. Spatial tools to renew planning paradigm through metropolitan agriculture. The case study of Turin (Italy) (Enrico Gottero) -- Chapter 16. Conclusion. Ten good reasons tofoster an innovative vision of agrarian urbanism in Europe (Enrico Gottero).
Keywords: Human geography; Agriculture; Biotic communities; Human Geography; Agriculture; Ecosystems